Bisociation of artistic and academic approaches in problem-based projects - Falk Heinrich (Journal of Problem Based Learning in Higher Education, 2018)
This article presents a theoretical elaboration of the potential relationship between the academic and artistic approaches within a problem-based educational setting. The investigation is based on Koestler’s idea of the “bisociation” (blending) of dissimilar thinking and action matrices as the foundational mechanism of human creation in academic discovering, artistic creation, and humour, respectively. On the basis of my own experiences with higher education pedagogy exemplified by a concrete workshop held with students from two different educational programmes at Aalborg University, the article investigates the bisociation of artistic and academic matrices and codes by scrutinising how these apparent incompatibilities could be functions of a blending mechanism. The article proposes that the bisociation of the artistic and academic approaches should be understood as mutual inscriptions leading to an emphasised correlation between academic abstractions and associative-emotional experiences leading to an increase in complexity, specifically, a multifaceted understanding and emotional perception of today’s societal challenges.